2016
DOI: 10.11604/pamj.2016.25.212.10414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of United States buckwheat honey on antibiotic-resistant hospital acquired pathogens

Abstract: IntroductionDue to an upsurge in antibiotic-resistant infections and lack of therapeutic options, new approaches are needed for treatment. Honey may be one such potential therapeutic option. We investigated the susceptibility of hospital acquired pathogens to four honeys from Wisconsin, United States, and then determined if the antibacterial effect of each honey against these pathogens is primarily due to the high sugar content.MethodsThirteen pathogens including: four Clostridium difficile, two Methicillin-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…One finding of major significance was the performance of buckwheat and avocado honeys, both of which outperformed manuka honey against each bacterium tested, with the exception of avocado against P. aeruginosa. These results are supported by the literature, where buckwheat honey has been shown to exhibit antibacterial activity comparable to or more potent than manuka [23][24][25][26][27][28][29]. Buckwheat has been shown to have higher concentrations of proteins, phenols, and minerals [27], and darker honeys are generally considered to be highly medicinal and have been found to have higher concentrations of pollen, total phenolics, minerals, and 5-hydroxymethylfurfural (HMF) [4].…”
Section: Discussionsupporting
confidence: 72%
“…One finding of major significance was the performance of buckwheat and avocado honeys, both of which outperformed manuka honey against each bacterium tested, with the exception of avocado against P. aeruginosa. These results are supported by the literature, where buckwheat honey has been shown to exhibit antibacterial activity comparable to or more potent than manuka [23][24][25][26][27][28][29]. Buckwheat has been shown to have higher concentrations of proteins, phenols, and minerals [27], and darker honeys are generally considered to be highly medicinal and have been found to have higher concentrations of pollen, total phenolics, minerals, and 5-hydroxymethylfurfural (HMF) [4].…”
Section: Discussionsupporting
confidence: 72%
“…Jiang et al (2020) reported that buckwheat honey positively affects intestinal microbes, which results in the increase in probiotics [7]. Hammond et al (2016) noted that antibiotic-resistant pathogens were susceptible to buckwheat honey originating from the USA [8]. Baranowska-Wójcik et al (2020) investigated 47 different honeys as a source for acetyl-and butyrylcholinesterase inhibitors (AChE and BChE), which are a possible therapeutic strategy in maintaining Alzheimer's disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…Buckwheat honey is known as "black honey" with sweet, delicious taste, long aftertaste, and unique malt flavor. Buckwheat honey seems to be one of the most valued honeys due to health benefits [3]. e abilities of buckwheat honey to promote health may be significantly correlated with its phenolic and carbohydrate compounds.…”
Section: Introductionmentioning
confidence: 99%